Numerical simulation of the electric field gradient squared in a new electrode configuration for fouling suppression in submerged membrane bioreactors / Bouthaina Larbi - Larbi, Bouthaina; Alhawari, Alaa; Du, Fei; Baune, Michael (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Fouling is one of the central problems in submerged membrane bioreactors (MBRs), and the use of additional forces for antifouling has gained increasing attention in the recent years. In this study, a novel fouling suppression system in MBRs based on the application of AC dielectrophoresis force is proposed. The feasibility of the new system is demonstrated based on numerical simulations. To this end, the impact of electrode configuration (i.e. electrode geometry, the distance between electrodes, insulation properties & insulation thickness) on the DEP force i.e. on the electric field gradient squared (EFG), are studied for an optimal design of the new system. It was found that the EFG is high on the membrane surface when the electrode diameter and the distance between electrodes are smaller. Obtained results also showed a drop of the electric field gradient squared at the mid between two electrodes with highest EFG value on the electrode. Finally, numerical simulations revealed that a thickness of 20 μm of TiO2 insulation is optimal to generate sufficient DEP force while avoiding joule heating problems.